Antenna and EM Modeling with MATLAB® Antenna Toolbox (2nd Edition) - Makarov, Sergey N.; Iyer, Vishwanath; Kulkarni, Shashank; Best, Steven R. (John Wiley & Sons, 2021)
Antenna and EM Modeling with MATLAB Antenna Toolbox™ is a textbook on antennas intended for a one semester course. The core philosophy is to introduce the key antenna concepts and follow them up with full-wave modeling and optimization in the MATLAB Antenna Toolbox™. Such an approach will enable immediate testing of theoretical concepts by experimenting in software. It also provides the direct path to research work. The fundamental families of antennas - dipoles, loops, patches, and traveling wave antennas - are discussed in detail, together with the respective antenna arrays. Using antenna parameters such as impedance, reflection coefficient, efficiency, directivity, and gain, the reader is introduced to the different ways of understanding the performance of an antenna. Written for senior undergraduates, graduates as well as RF/Antenna engineers, Antenna and EM Modeling with Antenna Toolbox™ is a resource that: Provides 14 video assisted laboratories on using Antenna Toolbox™; Includes approximately 50 real-world examples in antenna and array design; Offers approximately 200 homework problems; Provides multiple ready-to-use standalone MATLAB® scripts.